2005
DOI: 10.1002/bit.20432
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol production from glucose and dilute‐acid hydrolyzates by encapsulated S. cerevisiae

Abstract: The performance of encapsulated Saccharomyces cerevisiae CBS 8066 in anaerobic cultivation of glucose, in the presence and absence of furfural as well as in dilute-acid hydrolyzates, was investigated. The cultivation of encapsulated cells in 10 sequential batches in synthetic media resulted in linear increase of biomass up to 106 g/L of capsule volume, while the ethanol productivity remained constant at 5.15 (+/-0.17) g/L x h (for batches 6-10). The cells had average ethanol and glycerol yields of 0.464 and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 33 publications
5
44
0
Order By: Relevance
“…2A and B). In contrast, Martín and Jönsson (16) and Talebnia et al (22) reported that the relative ethanol productivity of S. cerevisiae is drastically reduced to 47% with 52 mM furfural or to 18% with 60 mM 5-HMF (Table 1). This indicates that our method employing growth-arrested C. glutamicum strain RldhA-pCRA723 showed greater tolerance to furfural and 5-HMF than other methods.…”
Section: Effect Of Individual Inhibitorsmentioning
confidence: 92%
“…2A and B). In contrast, Martín and Jönsson (16) and Talebnia et al (22) reported that the relative ethanol productivity of S. cerevisiae is drastically reduced to 47% with 52 mM furfural or to 18% with 60 mM 5-HMF (Table 1). This indicates that our method employing growth-arrested C. glutamicum strain RldhA-pCRA723 showed greater tolerance to furfural and 5-HMF than other methods.…”
Section: Effect Of Individual Inhibitorsmentioning
confidence: 92%
“…1B), low ethanol yields were observed. These low ethanol yields cannot be attributed to the presence of yeast inhibitors 15 since most of the inhibitors in pretreated substrates are removed during the washing step. Most likely, low ethanol yields can be explained as a result of low pulp consistency during enzymatic hydrolysis.…”
Section: Resultsmentioning
confidence: 95%
“…The low lignin amount in bio-pulps is associated with its removal during biological pretreatment and changes in macromolecule structure that facilitate its fragmentation and solubilization during pulping. 6,15 Pine bio-pulps contained approximately 40-50% less mannans than pulps produced from untreated wood. Xylans were less affected by bio-organosolv pulping and a decrease in its amount was mainly due to the hot alkaline wash of the pulp (P4).…”
Section: Resultsmentioning
confidence: 99%
“…5 The use synthetic or natural polymers to immobilize yeasts, as calcium alginate, carrageenin-oligochitosan, chitosan-carboxymethylcellulose, agarose, polyamide, among others, allows to protect the cells from inhibitors maintaining a high concentration of cells in the capsules, improving the thermal stability, maintaining a long time of operational stability of the encapsulated yeast and obtaining higher ethanol yields than in fermentations with the free yeast cells. 6,7 Saccharomyces cerevisiae is the yeast frequently used in the alcohol industry (wine, spirits and fuels) to ferment sugars from different kind of raw material such as grapes and other fruits, cereals, sugarcane, and lignocellulosic materials. The yeast is also used in researches of bio-elements bindings (e.g.…”
Section: Introductionmentioning
confidence: 99%